Molecular Impacts of Dietary Exposure to Nanoplastics Combined or Not with Arsenic in the Caribbean Mangrove Oysters (Isognomon alatus) - Marc Lebordais; Zélie Venel; Julien Gigault; Valerie S. Langlois; Magalie Baudrimont (Nanomaterials, 2021)
Nanoplastics (NPs) are anthropogenic contaminants that raise concern, as they cross biological barriers. Metals’ adsorption on NPs’ surface also carries ecotoxicological risks to aquatic organisms. This study focuses on the impacts of three distinct NPs on the Caribbean oyster Isognomon alatus through dietary exposure. As such, marine microalgae Tisochrysis lutea were exposed to environmentally weathered mixed NPs from Guadeloupe (NPG), crushed pristine polystyrene nanoparticles (PSC), and carboxylated polystyrene nanoparticles of latex (PSL). Oysters were fed with NP-T. lutea at 10 and 100 µg L−1, concentrations considered environmentally relevant, combined or not with 1 mg L−1 pentoxide arsenic (As) in water. We investigated key gene expression in I. alatus’ gills and visceral mass. NP treatments revealed significant induction of cat and sod1 in gills and gapdh and sod1 in visceral mass. As treatment significantly induced sod1 expression in gills, but once combined with any of the NPs at both concentrations, basal mRNA levels were observed. Similarly, PSL treatment at 100 µg L−1 that significantly induced cat expression in gills or sod1 in visceral mass showed repressed mRNA levels when combined with As (reduction of 2222% and 34%, respectively, compared to the control). This study suggested a protective effect of the interaction between NPs and As, possibly by decreasing both contaminants’ surface reactivity.